Length-Weight Relationship and Condition Factor of Three Populations of Coptodon zillii in Southwest, Nigeria - Oladimeji, Tofunmi Elizabeth; Akindolani, Gbenga Solomon; Aregbesola, Omolola Comfort; Ogbuebunu, Kikachukwu Emmanuel (Universitas Gadjah Mada, 2025)
The length-weight relationship and condition factor of Coptodon zillii from three different waterbodies (Aiba Reservoir, Asejire Reservoir, and Igbokoda River) in Southwest Nigeria were analyzed to determine the species' growth pattern and overall well-being. A total of 150 fish samples were collected from the landings of commercial fishermen. The length-weight relationship and condition factor (K) of the fish samples were determined following standard techniques. The study found that the three C. zillii populations exhibited negative allometric growth, with regression coefficients (b) values less than 3. This indicated that the fish's length increased at a faster rate than their weight. The condition factor (K) ranged from 1.92 to 2.03, suggesting that the fishes were in good health in their respective habitats. The variations in the mean condition factor values across the three populations suggested that the environmental conditions in the water bodies uniquely impacted the health and growth of the fish. These findings highlight the need for targeted fisheries management strategies to improve the sustainability of C. zillii populations in these aquatic systems.